Simulation of a surface-transverse wave (STW) biosensor for DF-1 cells - Nordin, Anis Nurashikin; Jamil, Nadira; Mel, Maizirwan; Voiculescu, Ioana; Ibrahimy, Muhammad Ibn (2010)
A 250 MHz Surface-Transverse Wave (STW) resonator is employed as a sensor element for the detection of DF-1 cells. STW belongs to the shear-horizontal acoustic plate modes (SH-APM) waves’ family where it has attracted plenty considerable interest. STWs are horizontally polarized shear waves which are generated and detected by the interdigital transducers (IDTs) similar to surface-acoustic wave (SAW) resonators [1]. Detection of chemical and biological agents in aqueous solutions is a difficult problem, especially when the detection technique has to be sensitive, power-efficient and very handy. Acoustic plate mode is a mode of vibration where particle motion is parallel to the surface. This makes it possible to produce a sensitive sensor capable of operating in fluids [2]. This paper presents the biosensor prototype utilizing STW resonator.